Simultaneous uptake of ammonium and phosphate ions by composites of y-alumina/potassium aluminosilicate gel - Okada, K.; Temuujin, Jadambaa; Kameshima, Y.; MacKenzie, K. (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The simultaneous uptake of ammonium and phosphate ions from solution by composites of g-alumina/potassium aluminosilicate (KAS) gel has been investigated. The composites were prepared by selective leaching of calcined kaolinite (Al2Si2O5(OH)4) using KOH solution, followed by neutralization of the leachate at pH 5.5 with nitric acid. The composites were reacted with solutions containing various concentrations of (NH4)2HPO4 at pH 5, 7 and 10 at room temperature for 24 h to examine their uptake of ammonium and phosphate ions. Simultaneous uptake of ammonium and phosphate ions was found, the uptake of ammonium ions being greater than for phosphate ions, especially at pH 7. This observation is considered to result mainly from the porous properties of the composites, which should therefore be controlled to enhance the simultaneous uptake of both ions, especially phosphate ion.